Determinants of Credit Decision in Consumer Financing: An Empirical Study on Indonesia Auto Financing - Suwinto Johan (Indonesian Journal of Business and Entrepreneurship (IJBE), 2018)
The aim of the research was to study the impacts of retail consumer’s 4 C (character, capacity, collateral and capital) on the credit quality performance of finance company. The credit quality of the consumer was analyzed using a behavior scoring system. The dependent variable was the credit quality, i.e. the non performing financing of more-than-90-day-payment due. The independent variables were the characteristics, capacity, collateral, and capital of the debtors. The samples were customers who got financing from 2013–2014 and were cut off due to delinquency by the end of 2015. Total samples were 750 customers who purchased 4 wheelers. In this research, the econometrics model was regression binary logistic model. In the model, the dependent variable was the dummy variable of customers whose delinquency was under 90-day payment due and was given 0, and the customers with delinquency more than 90-day payment due were given 1. The empirical results showed that collateral and capital had significant influence on credit quality. The collateral was represented by the title of the car ownership (title of ownership). The capital was represented by the financing tenor, at significance level = 0.05. The financing company should focus on the types of collateral, down payment, title of ownership and tenor of financing in determining credit decision.Keywords: consumer, credit, finance company, lending, logistic